Innovations in the treatment of type 2 diabetes mellitus: use of incretins - Ivan Ivanovich Dedov; Marina Vladimirovna Shestakova; Ol'ga Yur'evna Sukhareva; I I Dedov; M V Shestakova; O Yu Sukhareva (Терапевтический архив, 2010)
There is a new class of drugs used to treat diabetes mellitus (DM). It has come into existence after long-term studies of the fundamentally new hemostastic mechanism in glucose regulation via the gastrointestinal hormones incretins. With the advent of this class of drugs that minimize routine adverse reactions (weight gain, glycemic risk, nephro-, hepato-, and cardiotoxic effects, etc.), there is hope for a delay in the progressive increase of secretory function and β-cell mass, which is inevitable during standard treatment (which presages the eventual need to initiate insulin therapy 7-10 years after the onset of the disease). The mechanism of action of incretins is considered. The place of novel agents (glucagon-like peptide-1 receptor agonists and dipeptidyl peptidase-4 inhibitors) in the total pattern of treatment for type 2 DM, indications for and contraindications to their use, benefits versus traditional glucose-lowering therapy (the inestimable advantage of these drugs is no risk for hypoglycemia), and prospects for their future application are discussed.